A Pragmatic Analysis of Speech Acts Effects in Ada Apa Dengan Cinta? (2002) - Novia Nurfachri Anggraeni; Aini Nur Syafikha (Jurnal Multidisiplin Sahombu, 2026)
This study examines the pragmatic aspects of speech acts and their perlocutionary effects in the Indonesian film Ada Apa Dengan Cinta? (2002). Using selected dialogue scenes as data, the research focuses on how the characters’ utterances convey meaning, intention, and the resulting effect on listeners. The analysis applies Leech’s politeness principles and distinguishes between locutionary, illocutionary, and perlocutionary acts. Findings show that informal utterances, imperatives, and directives are frequently used to express emotions, assert authority, or influence others’ behavior. The study also reveals that the intended perlocutionary effects do not always align with the speaker’s goals, highlighting the complexity of interpersonal communication. This research provides insights into how pragmatic strategies function in real-life social interactions as represented in contemporary Indonesian cinema.